Targeting Protein Degradation in Cancer Treatment - Bjij, Imane; Hdoufane, Ismail; Soliman, Mahmoud; Najdoska-Bogdanov, Menče; Cherqaoui, Driss (Current Chemical Biology, 2021)
The ubiquitin proteasome system (UPS) is a crucial protein degradation pathway that involves several enzymes to maintain cellular protein homeostasis. This system has emerged as a major drug target against certain types of cancer as a disruption at the cellular level of UPS enzyme components forces the transformation of normal cell into cancerous cell. Although enormous advancements have been achieved in the understanding of tumorigenesis, efficient cancer therapy remains a goal towards alleviating this serious health issue. Since UPS has become a promising target for anticancer therapies, herein, we provide comprehensive review of the ubiquitin proteasome system as a significant process for protein degradation. Herein, the anti-cancer therapeutic potential of this pathway is also discussed.
Keywords: Ubiquitin proteasome system